Altered single-subject gray matter structural networks in first-episode drug-naïve adolescent major depressive disorder - Wu, Baolin; Chen, Ying; Long, Xipeng; Cao, Yuan; Xie, Hongsheng; Wang, Xiuli; Roberts, Neil; Gong, Qiyong; Jia, Zhiyun (Psychiatry research, 2023)
•This study is the first to perform a graph theory analysis of individual GM morphological networks in a relatively large sample of adolescent MDD patients.•Structural connectome analyses revealed disrupted small-world organization in adolescent MDD patients.•Adolescent MDD patients showed abnormal nodal centralities in the prefronal-subcortical-limbic areas and visual cortex regions.•Altered nodal centralities in the hippocampus were associated with illness duration and symptom severity. Although previous studies have demonstrated regional gray matter (GM) structural abnormalities in adolescents with major depressive disorder (MDD), how the topological organization of GM networks is affected in these patients is still unclear. Structural magnetic resonance imaging data were acquired from 100 first-episode drug-naïve adolescent MDD patients and 80 healthy controls (HCs). Whole-brain GM structural network was constructed for each subject, and a graph theory analysis was used to calculate the topological metrics of GM networks. Adolescent MDD patients showed significantly lower cluster coefficient and local efficiency compared to HCs. Compared to controls, adolescent MDD patients showed higher nodal centralities in the bilateral cuneus, left lingual gyrus, and right middle occipital gyrus and lower nodal centralities in the bilateral dorsolateral superior frontal gyrus, bilateral middle frontal gyrus, right anterior cingulate and paracingulate gyri, bilateral hippocampus, bilateral amygdala, bilateral caudate nucleus, and bilateral thalamus. Nodal centralities of the hippocampus were negatively associated with symptom severity and illness duration. Our findings suggest disrupted topological organization of GM structural networks in adolescent MDD patients. Impaired local segregation and abnormal nodal centralities in the prefrontal-subcortical-limbic areas and visual cortex regions may play important roles in the neurobiology of adolescent-onset MDD.